Bond characteristics of porcelain fused to cast and milled titanium - Karina Andrea Novaes Olivieri; Maximiliano Piero Neisser; Marco Antônio Bottino; Milton Edson Miranda (Universidade Estadual de Campinas, 2015)
Metalloceramic restorations combine the aesthetic properties of ceramic materials with the high strength of metals. The titanium has excellent biocompatibility, good mechanical properties and low density, and has been recently used for metalloceramic prosthesis. The purpose of this study was to evaluate the shear bond strength of these two materials, and also analyze their bonding interface using Scanning Electron Microscopy (SEM). Thirty-six specimens were prepared and divided in three groups: Group 1- gold alloy (Degudent U-Degussa) + Vita Omega 900 ceramic(Vita) (control group); Group 2 - milled commercially pure titanium (cpTiDentaurum) + Titankeramik ceramic (Vita); Group 3 - cast and milled commercially pure titanium (cpTi-Dentaurum) + Titankeramik ceramic(Vita). The shear bond strength mechanical assay was performed in an Instron 4301 machine with capacity for 500Kg. After the test completion, surfaces were evaluated using SEM. The numerical results, put in tables, were: G1= 40,55MPa (+/- 4,8), G2= 63,54 MPA (+/- 1,73) and G3= 68,17 MPA (+/- 1,19). The statistical analysis (ANOVA) showed no significant statistically differences between groups G2 and G3 and the values were larger (significant statiscally) than G1. It is concluded that the titanium alloys is a good alternative to gold alloys to metalloceramic restorations emphasizing that it is cheaper, biocompatible and is has a low density.